Indigenous Knowledge Systems employed in child health care in Manicaland: case of Mutare - Muzvidzwa, Caroline Tafadzwa (Midlands State University, 2018)
This study aims to research on the use of Indigenous Knowledge Systems employed in child health care with a case study of Mutare so as to reduce child mortality. The study also discusses the leading causes of child mortality in Mutare and the factors that contribute to increased child mortality like religious beliefs and cultures that do not support visiting clinics and hospitals. It looks at how effective are these IKS in addressing child mortality which is an issue of concern in development because children are significant for sustainable development.. This was made possible through conducting interviews as well as observatory study for key findings as to what methods are used by IKS experts in dealing with different child related diseases which result in mortality. Measures to counter weaknesses surrounding IKS will be discussed so as to mainstream IKS as a medical route to child health care to deal with the problem of child mortality in Mutare